2017
DOI: 10.1080/07370016.2017.1340554
|View full text |Cite
|
Sign up to set email alerts
|

GROW: Green Organic Vegetable Gardens to Promote Older Adult Wellness: a Feasibility Study

Abstract: Protecting older adult's cognitive health is a public health priority. Wellness behaviors within 6 domains have demonstrated effectiveness in protecting older adult's cognitive abilities. Interventions targeted to low-income older adults are needed because these populations experience greater social and physical health disparities compared to adults in higher socioeconomic statuses. This study examined the feasibility of engaging independent, community-dwelling older adults living in low-income senior housing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(33 citation statements)
references
References 38 publications
1
27
1
Order By: Relevance
“…As a result, these activities play a different role these days, adding cultural, social and physical values to their importance for agrarian and ecological processes [ 62 ]. Consequently, although existing literature emphasizes the benefits of growing your own produce for the mental and physical wellbeing of the elderly [ 63 , 64 , 65 ], the results of our study showed a limited impact of these practices on dietary patterns.…”
Section: Discussioncontrasting
confidence: 69%
“…As a result, these activities play a different role these days, adding cultural, social and physical values to their importance for agrarian and ecological processes [ 62 ]. Consequently, although existing literature emphasizes the benefits of growing your own produce for the mental and physical wellbeing of the elderly [ 63 , 64 , 65 ], the results of our study showed a limited impact of these practices on dietary patterns.…”
Section: Discussioncontrasting
confidence: 69%
“…Session frequency was variable, with weekly delivery most common (n = 13, 42%) (47-50, 54, 56, 63, 65-67, 69, 71, 75) . Interventionists included trained facilitators (n = 6, 19%) (48,52,66,70,73,75) , research personnel (n = 4, 13%) (55,56,61,68) , educators (n = 3, 10%) (54,58,71) , nutritionists (n = 3, 10%) (57,62,69) , physiotherapists and/or trainers (n = 3, 10%) (64,67,72) , registered dietitians (n = 2, 6%) (50,51) , healthcare providers (n = 2, 6%) (63,76) , lay leaders (n = 2, 6%) (53,77) , and peer leaders (n = 2, 6%) (60,74) . Four studies (13%) did not report interventionist details.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…Conversely, two additional studies that combined nutrition education with BCT did not improve nutritional status (moderate to high risk of bias) (57,72) . Two studies (low to moderate risk of bias) evaluated food access or nutrition education with BCT and food access (54,69) ; these did not consistently reduce nutrition risk.…”
Section: Nutrition Riskmentioning
confidence: 99%
See 2 more Smart Citations